FREQUENCY OF IRRITABLE BOWEL SYNDROME IN ADOLESCENTS WITH DEPRESSION: AN EXPERIENCE IN A TERTIARY CARE HOSPITAL - Waqas, Muhammad; Wazir, Nauman; Zeb, Salma; Iqbal, Muhammad (Journal of Postgraduate Medical Institute, 2016)
Objective: To determine the frequency of IBS in depressed adolescent patients. Methodology: The study, designed as a cross-sectional, was performed in a consecutive sample of adolescents diagnosed with depression in the Department of Medicine, Lady Reading Hospital, Peshawar, Pakistan. Frequency of IBS in depressed adolescents was found using the Rome III criteria. Results: Among 162 depressed adolescents, 73(45%) were male and 89(55%) were female. Overall 24(14.81%) of adolescents diagnosed with depression were having IBS. Among 162 adolescents, 49(30%) were having mild depression, of which 4(8.16%) were having IBS; 70(43%) were having moderate depression, of which 9(12.85%) were having IBS; 36(22%) were having moderate severe depression, of which 7(19.44%) were having IBS; 8(5%) were having severe depression, of which 4(50%) were having IBS. Conclusion: There was a high frequency of IBS in depressed adolescents and its frequency increased with the level of depression.